Neurofibromatosis Type 1 Associated with Hashimoto’s Thyroiditis: Coincidence or Possible Link - Junaid Nabi (Case Reports in Neurological Medicine)
Introduction. Hashimoto's thyroiditis is a common form of chronic autoimmune thyroid disease (AITD) and often coexists with other autoimmune diseases, but Hashimoto’s thyroiditis associated with an autosomal dominant neurofibromatosis type 1 is exceedingly rare. Case Presentation. A 30-year-old Bengali woman presented to the OPD with complaints of aching pain and tingling sensation in her hands and feet. Physical examination revealed dysmorphic facies, nodular swelling in the neck, cafe-au-lait spots, and neurofibromas covering the entire surface of her body. Her thyroid hormones were within normal limits. Thyroid ultrasound revealed a cystic area in the left lobe of the gland, and ultrasound-guided fine needle aspiration cytology revealed lymphocytic infiltration of the gland, suggesting Hashimoto’s thyroiditis. High levels of autoimmune antibodies such as antithyroglobulin and antimicrosomal antibodies confirmed the diagnosis. Conclusion. When encountered with a patient of Neurofibromatosis type 1, a physician should be careful about the possibility of a concomitant autoimmune disease. Clinical presentation of neurofibromatosis and Noonan syndrome often overlaps and recent studies have implicated a mutation in NF1 gene in the etiology of NFNS. More extensive reports and further investigations of such patients having combination of neurofibromatosis type 1 and autoimmune thyroiditis will certainly provide better understanding of this link in the near future.